MgO as a non-pyrolyzable pore former in porous membrane supports. Issue 9 (August 2018) - Haugen, A.B.; Geffroy, A.; Kaiser, A.; Gil, V.
Graphical abstract: Abstract: The gas permeability of Y0.03 Zr0.97 O2 (3Y-TZP) porous supports from thermoplastic feedstocks has been improved by adding MgO as a non-pyrolyzable pore former. Common pyrolyzable pore formers such as graphite often produce tortuous and narrow pore channels with low gas permeability, limiting the performance of oxygen transport membranes or other membranes relying on gas transport to the active membrane surface. Thermoplastic feedstocks for extrusion of tubular 3Y-TZP supports were prepared with four different amounts of pyrolyzable pore formers and/or MgO as non-pyrolyzable pore former. The MgO was removed after sintering by leaching in acetic acid. With this technique we obtained porosities above 70 vol% and gas permeabilities above 3∙10 −14 m 2 . Compared to samples with only pyrolyzable pore formers, the non-pyrolyzable pore former increases the gas permeability and reduces the tortuosity.